Association of Metabolic Syndrome with Aerobic Exercise and LPL rs3779788 Polymorphism in Taiwan Biobank Individuals - Hsu CS (Dove Medical Press, 2021)
Chun-Sheng Hsu,1– 4 Shin-Tsu Chang,1,5,6 Oswald Ndi Nfor,2 Kuan-Jung Lee,2 Chien-Chang Ho,7,8 Chuan-Ching Liu,1 Shiuan-Shinn Lee,2 Yung-Po Liaw2,9 1Department of Physical Medicine and Rehabilitation, Taichung Veterans General Hospital, Taichung City, 40201, Taiwan; 2Department of Public Health and Institute of Public Health, Chung Shan Medical University, Taichung City, 40201, Taiwan; 3School of Medicine, National Defense Medical Center, Taipei City, 11490, Taiwan; 4College of Medicine, National Chung Hsing University, Taichung City, 402, Taiwan; 5Department of Physical Medicine and Rehabilitation, Tri-Service General Hospital, School of Medicine, National Defense Medical Centre, Taipei City, 11490, Taiwan; 6Department of Physical Medicine and Rehabilitation, Kaohsiung Veterans General Hospital, Kaohsiung City, 813414, Taiwan; 7Department of Physical Education, Fu Jen Catholic University, New Taipei, 24205, Taiwan; 8Research and Development Center for Physical Education, Health, and Information Technology, Fu Jen Catholic University, New Taipei, 24205, Taiwan; 9Department of Medical Imaging, Chung Shan Medical University Hospital, Taichung City, 40201, TaiwanCorrespondence: Yung-Po Liaw; Shiuan-Shinn LeeDepartment of Public Health and Institute of Public Health, Chung Shan Medical University, No. 110 Sec. 1 Jianguo N. Road, Taichung City, 40201, TaiwanTel +886 424730022 ext. 11838; +886 424730022 ext.12185Fax +886 423248179Email Liawyp@csmu.edu.tw; shinn@csmu.edu.twPurpose: The Lipoprotein lipase (LPL) gene is a significant contributor to dyslipidemia. It has shown associations with several conditions including atherosclerosis, obesity, and metabolic syndrome (MetS). We assessed the interactive association between MetS and rs3779788 of the LPL gene based on aerobic exercise.Materials and Methods: Data were available for 7532 Taiwan Biobank (TWB) participants recruited between 2008 and 2016. We used multiple logistic regression to determine the odds ratios (OR) for MetS and their 95% confident intervals (C.I.). Potential variables included LPL rs3779788, aerobic exercise, sex, age, education, marital status, body mass index (BMI), smoking, alcohol consumption, midnight snacking, vegetarian diet, coffee, dietary fat, and tea drinking.Results: Aerobic exercise was protective against MetS (OR, 0.858; 95% C.I., 0.743– 0.991). Compared to CC/CT genotype, the OR for developing MetS was 0.875, (95% C.I., 0.571– 1.341) in TT individuals. The test for interaction was significant for the rs3779788 variant and aerobic exercise (p = 0.0484). In our group analyses, the OR for MetS was 0.841 (95% C.I., 0.727– 0.974) in CC/CT and 4.076 (95% C.I., 1.158– 14.346) in TT individuals who did aerobic exercise compared to those who did not.Conclusion: Our study indicated that aerobic exercise improved metabolic syndrome in Taiwanese adults with rs3779788 CC/CT genotype relative to those with TT genotype.Keywords: polymorphisms, variant, physical activity, metabolic disorders